Pengaruh Ekspektasi Kinerja, Ekspektasi Usaha, FaktorSosial, Kesesuaian Tugas Dan Kondisi Yang Memfasilitasi Pemakai Terhadap Minat Pemanfaatan Sistem Informasi(Studi Pada Bank Pengkreditan Rakyat Di Kabupaten Karanganyar) - Ningrum, Triyas Wendah, Dr. Noer Sasongko, SE, M.Si, Ak (2016)
This study aimed to examine the effect of performance expectations, effort expectations, social factors, the suitability of the duties and conditions that facilitate user to the interest of using of information systems. The variables used in this study is the expectation of performance, effort expectation, social factors, the suitability of duties, conditions which facilitate the users and the interest of using of information systems. The populationthis study is staff Bank Pengkreditan Rakyat ( BPR ) in Karanganyar. The Samples in this research is all employees accounting department and finance department.The sampling technique in this research with used purposive sampling method. The study had 50 samples of 7 BPR. In this study, the hypothesis was tested by using multiple linear regression. The results of this study indicate that the performance expectations affect the interest of using of information systems with a significance level of 0.033 <0.05. So, the first hypothesis is accepted. The effortexpectationsinfluence the interest of using information systems with a significance level of 0.037 <0.05. So, the second hypothesis is accepted. Social factors influence the interest of using information systems with a significance level of 0.046> 0.05. So, the third hypothesis is accepted. The duty suitabilitiesinfluence the interest of using information systems with a significance level of 0.024> 0.05. So, the fourth hypothesis is accepted. The conditions that facilitate the usersinfluence the interest of usinginformation systems with a significance level of 0.002> 0.05. So, the fifth hypothesis is accepted.